Effect of Plant Preservative MixtureTM on Endophytic Bacteria Eradication from In Vitro-Grown Apple Shoots - Natalya V. Romadanova; Arman B. Tolegen; Svetlana V. Kushnarenko; Elena V. Zholdybayeva; Jean Carlos Bettoni (Plants, 2022)
Endophytic contaminants are a common problem for the in vitro propagation of woody plants and have significant economic repercussions for the conservation of plant genetic resources and commercial micropropagation. In this study, first, the microbial contamination that appeared around the base of in vitro-grown apple shoots was identified as Bacillus megaterium. Then, plant preservative mixture (PPMTM) was used as a bactericidal agent in plant tissue culture. Its efficacy for eradicating endophytic B. megaterium in in vitro cultures of apple was tested. In vitro-contaminated shoots were grown in tissue culture medium supplemented with 0.2% v/v PPMTM for 12 weeks and then transferred to medium without any PPMTM and cultured for 24 weeks. This study showed that PPMTM is an effective agent for controlling the growth of B. megaterium. Our results highlight the species-specific response of apple shoots to PPMTM. PPMTM was effective in controlling endogenous microbial contaminations from apple varieties ‘Golden Delicious’, ‘Landsberger Renette’, ‘Suislepper’, and ‘Aport krovavo-krasnyi’; meanwhile, in ‘KG 7’ and ‘Gold Rush’, all the plants grown in the absence of PPMTM were still bacterially contaminated, even though they were pre-treated for 12 weeks in PPMTM-supplemented medium. These results therefore suggest the essentiality of further testing of extended incubation of PPMTM in these cultivars that had outbreaks of bacterial contamination.